THE DEVELOPMENT OF ENGLISH ADJECTIVES FROM OLD ENGLISH TO MODERN ENGLISH - Albertus Suwardi (Soegijapranata Catholic University, 2007)
This paper discusses the development of adjectives in Old English, Middle English, and Modern English. In the discussion it is found that the Old English'adjectives had inflectional modification to indicate numbers, genders, cases, and degrees of comparisons, and there was a distinction of weak and strong declensions. In Middle English, most of the declensional distinctions were lost, the general tendency of the language being to drop all suffixes. Adjectives in Modem English do not change their forms to show changes in number. case, or gender; and only, a few adjectives o/the pronominal class possess meanings which indicate number. One, and every, each modify singular nouns while several. few. many modify, only plural substantives. I